A philosophical enquiry into the origin of our ideas of the sublime and beautiful - Burke, Edmund (Oxford University Press, 2008)
An eloquent and sometimes even erotic book, the Philosophical Enquiry was long dismissed as a piece of mere juvenilia. However, Burke's analysis of the relationship between emotion, beauty, and art form is now recognized as not only an important and influential work of aesthetic theory, but also one of the first major works in European literature on the Sublime, a subject that has fascinated thinkers from Kant and Coleridge to the philosophers and critics of today. This is the only available edition of the work. ABOUT THE SERIES: For over 100 years Oxford World's Classics has made available the widest range of literature from around the globe. Each affordable volume reflects Oxford's commitment to scholarship, providing the most accurate text plus a wealth of other valuable features, including expert introductions by leading authorities, helpful notes to clarify the text, up-to-date bibliographies for further study, and much more.